(untitled) (The Journal of Building and Land Development, 2023)
Informal construction practices contribute substantially to construction sector. On the other hand, specification of building materials defines the quality of materials used, construction methods and quality of the workmanship. Knowledge transfer on building materialâ€™s specification between workersâ€™ mentor and mentees in informal construction practices may be at jeopardy. As such informality is rarely in favour of explicit knowledge transfer on building materials specifications. This study has analysed knowledge transfer on specification of building materials based on social capital and motivation theories. Social capital variables are presumed to support the knowledge transfer but jeopardises quality of finished housing units while motivations outside the social capital frameworks are useful for the final output they do not support adequate knowledge transfer. Findings suggest that informal knowledge transfer on specification of building materials is on first instance motivation driven through factors such as employability, quality of works and performance. However, social capital actors and interactions determine the final knowledge transfer output. Thus motivation drive informal knowledge transfer on the specification of building materials as a technical response to market demands, while social networks determine quality of built units. The two are inseparable in as far as informal construction practices are concerned. Â Keywords: Informal construction, Knowledge Transfer, Building material, Specifications